Architectural design based on energy efficiency criteria in housing in Villa El Salvador - Huamani Mendoza, Jackelyn Esthefany (2025)
Villa El Salvador, on the outskirts of Lima, faces challenges due to urban growth and energy demand. Therefore, it is essential to implement sustainable and energy-efficient strategies in housing to reduce consumption without compromising residents' comfort or quality of life. Architectural optimization includes proper building orientation, the use of insulating materials, natural ventilation, and renewable technologies. These measures can reduce energy consumption and CO2 emissions, generating economic savings and increasing resilience to climate change. The study evaluates the application of these criteria in housing, demonstrating that energy efficiency is key to the district's sustainable development. A comprehensive search was conducted using a combination of key terms related to architectural optimization in housing for energy efficiency, and a time limit was set to include studies published between 2020 and 2024 to ensure the relevance of the research. 30 articles were reviewed, both nationally and internationally, of which 19 were excluded for not providing adequate information for the analysis. After collecting the data, the information was analyzed, classifying 11 articles that met the relevant criteria, which will be integrated into the following article. The relevant information was obtained by searching databases specialized in architectural design based on energy efficiency criteria in homes in Villa El Salvador. The main databases consulted were ProQuest, Alicia, ScienceDirect and Google Scholar.